The Integral Role of Accounting in Organizational Dynamics and Decision-Making - Ermawati, Yana (Advances in Applied Accounting Research, 2023)
Purpose: The purpose of this research is to explore the integral role of accounting in organizational dynamics and decision-making processes. Research Design and Methodology: The study employs qualitative research methodology, conducting a systematic review of the literature. The research design involves structured searches across academic databases and online repositories, utilizing predefined search terms and inclusion criteria. The primary data collection method is a systematic review of the literature, supplemented by citation chaining and scanning of reference lists to enhance the breadth and depth of the literature review. Findings and Discussion: The findings reveal that accounting plays a multifaceted role in organizational dynamics, encompassing financial management, governance, risk management, and strategic decision-making. Transparent and reliable financial reporting serves as a foundation for stakeholders to assess organizational performance and make informed decisions. The integration of non-financial performance measures alongside financial metrics enhances the effectiveness of decision-making and strategic alignment. Implications: The study emphasizes the importance of continuous adaptation and innovation in accounting practices for effectively navigating evolving business environments. Moreover, technological advancements, globalization, and regulatory reforms have a significant impact on accounting practices and organizational dynamics, presenting both opportunities and challenges.